Artes plásticas e jornalismo cultural, reflexos da pós-modernidade : Ilustríssima, Revista Cult e Digestivo Cultural - Rossetti, Micaela Lüdke (2016)
Brazilian cultural journalism, as committed to the evaluation of ideas, values and arts, finds itself in an unprecedented moment of its history: the postmodern context enables the coexistence of several channels of expression and also exerts influence over the journalistic practice and the creation of artistic works within several fields. Among them, plastic arts deserve special attention due to their capacity to reflect on the present moment and act as a motor for social changes. This paper aims to identify, by applying the technique of content analysis (BARDIN, 2009), the treatment received by plastic arts from three of the country’s leading vehicles of cultural journalism: the cultural supplement Ilustríssima, published on Sundays by Folha de São Paulo; Revista Cult, published monthly by Editora Bregantini; and the website Digestivo Cultural, created and updated daily by Julio Daio Borges. Our research reveals the presence or absence of postmodern characteristics in the relations between art and cultural journalism, as well as in the exercise of both practices. In order to support our arguments, we have resorted to the reflections of Guy Debord, Jean-François Lyotard, Michel Maffesoli, Fredric Jameson, Zygmunt Bauman and Gilles Lipovetsky. This essay further infers comparisons between the nature, production regime and content of the channels studied, with the purpose of evincing the peculiarities of each dispositive and, consequently, exploring the contemporary situation of Brazilian cultural journalism.